The hypnotic effect of propofol involves inhibition of GABAergic neurons in the lateral hypothalamus. Issue 14 (9th October 2019) - Shi, Yihua; Xiao, Deshuang; Dai, Lingbo; Si, Yongyu; Fang, Qian; Wei, Xing
Abstract : Propofol is widely used for induction and maintenance of anaesthesia, which causes a rapid loss of consciousness. So far the mechanisms underlying the effect of propofol are still largely unknown. Here, we found that microinjection of propofol in the lateral hypothalamus caused a significant decrease in wakefulness and an increase in the amount of non-rapid eye movement sleep and rapid eye movement sleep. Application of propofol in the lateral hypothalamus affected the electroencephalogram power spectra with a decrease in theta oscillations and an increase in the delta oscillations. Additionally, using whole-cell patch clamp recording, we found propofol inhibited the excitability of the GABAergic neurons in the lateral hypothalamus, which plays a critical role in controlling wakefulness. Altogether, these findings indicate that propofol targets lateral hypothalamus and generates a hypnotic state, which might involve the inhibition of GABAergic neurons. These results provide a novel mechanism to explain propofol-elicited anaesthesia.